2016
DOI: 10.1002/hyp.11061
|View full text |Cite
|
Sign up to set email alerts
|

Large scale climate and rainfall seasonality in a Mediterranean Area: Insights from a non‐homogeneous Markov model applied to the Agro‐Pontino plain

Abstract: In the context of climate change and variability, there is considerable interest in how large scale climate indicators influence regional precipitation occurrence and its seasonality. Seasonal and longer climate projections from coupled ocean-atmosphere models need to be downscaled to regional levels for hydrologic applications, and the identification of appropriate state variables from such models that can best inform this process is also of direct interest. Here, a Non-Homogeneous Hidden M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…In the last three decades, many studies have addressed the issue of climate evolution under anthropic pressure [1]. An increase of the annual mean global temperature and changes of other climate parameters have been observed in the last century [2][3][4][5]. In fact, many papers particularly concern global climate modelling and the recent warming due to human activity.…”
Section: Introductionmentioning
confidence: 99%
“…In the last three decades, many studies have addressed the issue of climate evolution under anthropic pressure [1]. An increase of the annual mean global temperature and changes of other climate parameters have been observed in the last century [2][3][4][5]. In fact, many papers particularly concern global climate modelling and the recent warming due to human activity.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of numerical models representing the physical processes in the atmosphere, ocean, cryosphere and land surface simulate the response of the global climate systems to increasing greenhouse gas concentrations and forecast how the climate is expected to change until 2050 and 2070 [1]. A recent study using a non-homogenous Markov model shows that the best atmospheric predictor variables are mean sea level pressure, temperatures at 1000 hPa, meridional and zonal winds at 850 hPa and precipitation at the latitude of 20 • N to 80 • N and longitude of 80 • W to 60 • E [2]. Wilby and Dawson [3] suggest that a focus on physically meaningful quantities, such as wind speeds, wave heights, phenological and hazard metrics, could improve our understanding of downscaled models.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used daily rainfall amount because previous studies [11,35] have shown that 24-h-long heavy rainfall (with a daily rainfall amount greater than 100 mm) has in the past induced serious flash flooding in the examined site. It should also be underlined that downscaling models aimed to project future changes in the precipitation regime [10] generally refer to the daily rainfall amount, and therefore it is reasonable to use the return period associated to such a quantity.…”
Section: Sets Of Pareto Optimal Solutions For Heavy Rainfall Events Amentioning
confidence: 99%
“…As a number of authors suggest, such methodologies must evolve to address "change" from climate variability at the global scale to local human impacts [8,9]. Recently, rainfall downscaling models have been constructed to perform projections of rainfall occurrence and amount at the basin level, under different global warming scenarios simulated by global or regional circulation models (GCMs and RCMs) [10,11]. Therefore, such models can be used to provide the hydrological inputs necessary to run hydraulic models to assess the reliability of existing hydraulic infrastructures, and eventually the design of new ones, to manage future flooding risk at the local scale.…”
Section: Introductionmentioning
confidence: 99%